2013
DOI: 10.1016/j.nrleng.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the clinical use of motor evoked potentials in multiple sclerosis

Abstract: Objective: To establish clinical guidelines for the clinical use and interpretation of motor evoked potentials (MEP) in diagnosing and monitoring patients with multiple sclerosis (MS). Recommendations for MEP use and interpretation will help us rationalise and optimise resources used in MS patient diagnosis and follow up. Method:We completed an extensive literature review and pooled our own data to produce a consensus statement with recommendations for the clinical use of MEPs in the study of MS.Results: MEPs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Latency is highly influenced by conduction properties and synaptic delays at central (cerebral and spinal) and peripheral divisions of the nervous system (Fernández et al 2013). Bergmann et al (Bergmann et al 2012) triggered spTMS over M1 during non-REM sleep according to the phase of spontaneous (> 1 Hz) neocortical slow oscillations (SO) to show that MEPs were larger and their latencies were shorter during SO up-states than during down-states, which revealed that MEP latency can be modulated by brain states.…”
Section: One Disadvantage Of Meps To Evaluate the Physiological Mechamentioning
confidence: 99%
“…Latency is highly influenced by conduction properties and synaptic delays at central (cerebral and spinal) and peripheral divisions of the nervous system (Fernández et al 2013). Bergmann et al (Bergmann et al 2012) triggered spTMS over M1 during non-REM sleep according to the phase of spontaneous (> 1 Hz) neocortical slow oscillations (SO) to show that MEPs were larger and their latencies were shorter during SO up-states than during down-states, which revealed that MEP latency can be modulated by brain states.…”
Section: One Disadvantage Of Meps To Evaluate the Physiological Mechamentioning
confidence: 99%
“…MRI techniques have diminished their spectrum of use, although visual and motor EPs may have some utility as biomarkers of neurodegeneration [160]. Motor EPs are of special value in patients with MS presentation as a spinal cord syndrome [161]. Sensory EPs in combination with EDSS score could help in predicting short-term progression of disability in MS [162].…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…According to recommendations from Fernández et al [ 36 ], MEP studies are considered the first choice in patients with symptoms that are compatible with the first episode of demyelinating diseases, in patients with a clinical diagnosis of MS, and normal or inconclusive results from a brain MRI. Further, since the functional pyramidal EDSS score was shown to be the most frequently associated with sustained disability progression, it might be relevant to report functional pyramidal EDSS scores together with the overall EDSS score.…”
Section: Discussion On Some Practical and Technical Guidelines For Im...mentioning
confidence: 99%
“…Recommendations for the clinical use of MEPs in MS are reported by Fernández et al [ 36 ], and mainly discuss the application of TMS with no navigation for the use of MEP assessment in pwMS. The majority of reported studies ( Table 1 ), assessing the MEP in pwMS, used TMS apparatus with no navigation.…”
Section: Assessment Of Meps In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation